Year-long, multiple-timepoint field studies show the importance of spatiotemporal dynamics and microbial functions in agricultural soil microbiomes - Lisa Joos; Sarah Ommeslag; Steve Baeyen; Wouter Asselberg; Koen Van Loo; Lieven Clement; Jane Debode; Bart Vandecasteele; Caroline De Tender (mSystems)
ABSTRACT Despite the recognition of the complexity of soil ecosystem dynamics, most soil microbiome studies sample one field, take one sample per field, or use limited samples throughout the year. This limits our understanding of the spatiotemporal role of the soil microbiome in relation to management practices. To address these limitations, we conducted a year-long investigation of the soil microbiome in two agricultural fields, sampling multiple plots at different soil depths every 5 weeks. We examined spatial and temporal variabilities in response to the application of organic amendments (one-time biochar and annual compost application) on bacterial and fungal communities, studying both the microbial composition (metabarcoding, phospholipid fatty acids [PLFA], hot-water extractable-carbon) and activity (metatranscriptomics). Indicated by metabarcoding and PLFA, fungal communities were less affected over time per field, whereas bacteria exhibited more pronounced temporal trends. In contrast, fungi displayed clear spatial effects, while bacterial spatial differences within the field were predominantly observed in the deeper soil layer. Effects on functional roles and metabolic processes of the active microbial community were mainly related to temporal trends, especially in the topsoil. Organic amendments did not affect the microbial activity and affected fewer than 2% of the bacterial and fungal amplicon sequence variants over time. This study reveals the predominance of spatiotemporal dynamics over management practices in shaping soil microbial communities within agricultural fields, emphasizing the importance of field-specific factors, sampling depth, and community type. This ushers in the need for a well-considered experimental design and sampling strategy that accounts for spatiotemporal trends.IMPORTANCEThis study addresses a critical gap in soil microbiome research by investigating spatiotemporal effects on soil bacterial and fungal composition and activity in relation to field management practices. Moving beyond single-field and limited sampling approaches, this research conducted monthly sampling events on two fields at various depths. By combining metabarcoding, phospholipid fatty acid analysis, and metatranscriptomics, the study examined bacterial and fungal community composition, biomass, and functionality. Key findings reveal distinct responses of bacterial and fungal communities to spatiotemporal variability and management practices. Functional categories were predominantly driven by temporal trends rather than compost amendments. Temporal changes were more pronounced in the topsoil. These insights into the complex interactions between soil microbial communities, management practices, and spatiotemporal dynamics contribute significantly to soil microbiome research and sampling strategies.